2020
DOI: 10.1111/1365-2745.13496
|View full text |Cite
|
Sign up to set email alerts
|

Addition of nitrogen to canopy versus understorey has different effects on leaf traits of understorey plants in a subtropical evergreen broad‐leaved forest

Abstract: Atmospheric nitrogen (N) deposition has substantial effects on forest ecosystems. The effects of N deposition on understorey plants have been simulated by spraying N on the forest floor. Such understorey addition of N (UAN) might simulate atmospheric N deposition in a biased manner, because it bypasses the canopy. We compared the effects of UAN and canopy addition of N (CAN) at 0, 25 and 50 kg N ha−1 year–1 on SLA, leaf construction costs (CC), concentrations of leaf carbon ([C]), nitrogen ([N]), phosphorus ([… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 67 publications
(131 reference statements)
1
15
1
Order By: Relevance
“…In this study, leaf NSCs, starch, and total soluble sugar concentrations showed less variation with treatments ( Figure 2 ), which was consistent with the findings of other studies ( Li et al., 2018 ; Mo et al., 2020 ; Tang et al., 2020 ). Previous studies have implied that the N and P levels in leaves can influence the production of NSCs ( Xie et al., 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, leaf NSCs, starch, and total soluble sugar concentrations showed less variation with treatments ( Figure 2 ), which was consistent with the findings of other studies ( Li et al., 2018 ; Mo et al., 2020 ; Tang et al., 2020 ). Previous studies have implied that the N and P levels in leaves can influence the production of NSCs ( Xie et al., 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…The traditional method is mainly to add N directly to the understory, but this ignores the N interception effect of the forest canopy ( Tian et al., 2019 ; Tang et al., 2020 ). In this experiment, we selected two dominant tree species in a temperate forest to conduct multi-year canopy N addition and precipitation enhancement, and we determined the effect of N and water addition on NSCs and leaf long-term WUE in the dominant tree species in the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…Understory N-addition experiment overlooks the absorption, retention, and transformation of N by forest canopy and thus may overestimate the effect of atmospheric N addition on forest soils (Lu et al, 2021). Recent canopy N-addition studies suggest that canopy N addition and understory N addition have different effects on tree growth (Tang et al, 2020), soil microbial properties (Liu et al, 2020), and soil C dynamics (Lu et al, 2021). These findings have implications for future research to examine the potential effects of forest canopies in simulated N deposition experiments.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Plants may also delay their reproductive phenology to adapt to environmental changes such as a decreasing nutrient supply [ 15 , 16 ]. However, studies to date have concentrated mainly on the responses of dominant species, with research gaps on the impact of the N deposition on the functional traits of REFs [ 3 , 5 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, among growth, defense, and reproductive traits, previous studies including simulated N deposition have mainly focused on growth response (rather than defense or reproduction) in forest ecosystems [ 17 , 19 , 20 ], with inconsistent conclusions. For example, N addition directly enhanced leaf N and P concentrations, but declines or non-significant changes in leaf N and P concentrations were also found [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%